Theoretical ionization and capture cross sections for DNA nucleobases impacted by light ions - Champion, Christophe (2012)
Although DNA lesions are considered of prime importance for describing the post-irradiation cellular survival, they still remain rarely studied on both experimental and theoretical sides. Under these conditions, we here propose different theoretical models for predicting the single ionization and single capture total cross sections for DNA bases impacted by protons.Material and methods: Three theoretical approaches are developed: a first classical one based on a classical trajectory Monte Carlo (CTMC) model and two quantum mechanical ones, namely, a Coulomb Born (CB1) and a continuum-distorted wave eikonal-initial-state (CDW-EIS) model. Results: Ionization and capture processes induced by protons on DNA bases (adenine, cytosine, thymine and guanine) are here studied in terms of total cross sections. Conclusions: A very good agreement is obtained between the different models at high enough impact velocities but discrepancies are observed between them at low impact energies (Ei<100 keV). Furthermore, it is shown that the theoretical cross sections underestimate the rare existing experimental data in particular for adenine and thymine whereas a reasonable agreement is found for cytosine.